2021
DOI: 10.1186/s13034-021-00418-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in young adults' mental well-being before and during the early stage of the COVID-19 pandemic: disparities between ethnic groups in Germany

Abstract: Background The COVID-19 pandemic resulted in substantial disruptions to the daily lives of young people. Yet knowledge is lacking about changes in mental well-being among young adults, whether those from ethnic minorities were more adversely impacted by the pandemic than the ethnic majority, and the extent to which pandemic-related stressors contributed to any declines in mental well-being. Methods We draw on nationally representative German CILS4C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Although both the groups deviated from healthy proportions of 80%, 10%, and 10%, the deviation was greater in the COVID-19 group with the proportion in the 'abnormal' category being 16.47%. This observation matches with the Plenty et al suggesting that young adults who reported contact with COVID-19, financial worries, and health worries experienced increased anxiety and depression [29]. For 'impact' scores both the groups were unhealthy.…”
Section: Association Between the 'Impact' And The 'Difficulty' Scoressupporting
confidence: 88%
“…Although both the groups deviated from healthy proportions of 80%, 10%, and 10%, the deviation was greater in the COVID-19 group with the proportion in the 'abnormal' category being 16.47%. This observation matches with the Plenty et al suggesting that young adults who reported contact with COVID-19, financial worries, and health worries experienced increased anxiety and depression [29]. For 'impact' scores both the groups were unhealthy.…”
Section: Association Between the 'Impact' And The 'Difficulty' Scoressupporting
confidence: 88%
“…For instance, people may experience pandemic-related stress due to isolation [ 1 ], unpredictability and daily routine disruptions, increased exposure to information about threats to well-being [ 10 ], and illness, unexpected loss and grief [ 22 ]. Pandemic-related stress subsequently negatively affects mental health [ 3 , 16 , 23 ]. Given the pre-existing risk factors in multi-problem families [ 6 , 7 ], these families are more likely to experience pandemic-related stress [ 4 , 21 ].…”
Section: Mental Health During the Covid-19 Pandemicmentioning
confidence: 99%
“…The present qualitative study aims to contribute by adopting a strength-based approach to explore how emerging adults perceive their socio-emotional development during the COVID-19 pandemic. Findings supplement statistical results on the impact of the COVID-19 pandemic on the emotional health of emerging adults (Alt et al, 2021;Liu et al, 2020;Plenty et al, 2021;Sun et al, 2020) by identifying socio-emotional developmental gains from the perspective of emerging adults themselves.…”
Section: Introductionmentioning
confidence: 66%
“…However, despite a growing body of evidence concerning how young people processed their COVID-19 related experiences (Ewing et al, 2022; Farris et al, 2021; Hussong et al, 2021; Velez et al, 2023) little is known about their socio-emotional development from their perspective. Furthermore, previous studies focused mostly on stress factors and negative emotions (Alt et al, 2021; Farris et al, 2021; Plenty et al, 2021), mental health (Ewing et al, 2022; Padilla-Walker et al, 2022; Rogers et al, 2021; van den Berg et al, 2021) and are mainly addressing coping with the first wave of the pandemic (Hussong et al, 2021; Plenty et al, 2021; van den Berg et al, 2021). The present qualitative study aims to contribute by adopting a strength-based approach to explore how emerging adults perceive their socio-emotional development during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%